Application of Web-Based Certainty Factor Method To Developo An Employee Job Stress Diagnosis System To Improve Employee Performance - Nurimansjah, Ris Akril (SEULANGA SYSTEM PUBLISHER, 2023)
This research aims to find out how to build an expert system for diagnosing work stress in employees using the certainty factor method. The data obtained was obtained in the following ways: Literature study, interviews, and questionnaires The population in this research is all employees. The sample for this research was 100 employees. The system development method used consists of requirements plan, system design, and implementation. Based on the research results, it was found that the expert system for diagnosing employee work stress uses the certainty factor method, which is easy for users to understand in presenting questions and results by employees, and the system can process data on symptoms, causes, and solutions because employees only select symptoms and do not enter them. symptom values that make users less understanding. This expert system has consistent answers. If you try to select the same symptoms, the results will be the same and in accordance with the expert's results.